The Difference of Mood Structure Analysis Between Male and Female Lecture Talk at IAIN Zawiyah Cot Kala Langsa - Kandri, Kandri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2024)
Study aims at analyzing male and female lecturer talk in EFL classroom. Theanalysis was meant to find out the realization of mood in lecturer talk, the realization of mood in lecturer's role, and the mood realization difference between male and female lectures talk in EFL classroom. It was designed as a descriptive — qualitative research, and discourse analysis. Data were collected through observations i.e. recording and note- taking as the main source. The data were 'analyzed using mood structure analysis suggested by M.A.K Halliday. To gain deeper analysis, the data were triangulated by interviewing the participants, two senior English lecturers' i.e. male and female lecture, and one linguist. Based on •the results of the data analysis, the findings of this research can be stated as follow: (I) male lecturer employed/ seven speech functions and female lecturer •employed eight speech functions during their classroom interaction. Those speech functions were commonly realized in two types: typical clause mood and nontypical clause mood in making interpersonal meaning among the student, (2) the dominant use almost all speech functions in a certain role i.e. a controller role indicates that there is a relation between lecture's role and mood realization (3) there are some differences of male and female lecture talk in selecting mood system in expressing interpersonal meaning to the student i.e. in giving information, in asking a question, in demanding the student to do something and in offering something to students. Cultural and social factor of the lecturers are believed as the contributions to the differences.